The Determinants of Strike Activity: An Interindustry Analysis - Maki, Dennis; Strand, Kenneth (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The paper presents an adaptation of a Chamberlain-Kuhn costs of agreement-costs of disagreement model explaining strike incidence and duration as functions of economic factors. The emphasis is on testing this model, rather than «explaining» strike activity. The results indicate the economic model fails to explain strike incidence, but does better at explaining strike duration, given incidence.